Communicating a diagnosis of dementia: A systematic mixed studies review of attitudes and practices of health practitioners. (November 2019) - Low, Lee-Fay; McGrath, Margaret; Swaffer, Kate; Brodaty, Henry
The aim of this study is to systematically review practitioners' practices and attitudes in regards to communicating a diagnosis of dementia. A systematic search was conducted of Scopus, Web of Science and PubMed for English language original empirical papers. A sequential explanatory mixed studies analysis approach was used. Twenty-five quantitative descriptive, two intervention, six mixed methods descriptive and 21 qualitative studies were included. Pooled analysis showed that 34% of GPs and 48% of specialists usually/routinely tell the person with dementia their diagnosis, and 89% of GPs and 97% specialists usually/routinely tell the family the diagnosis. Euphemistic terms such as 'memory problems' are more often used to describe dementia than medical terms. Practitioners' decision to diagnose and communicate the diagnosis of dementia are influenced by (a) their own beliefs regarding dementia and treatment efficacy and their confidence in diagnosis and communication; (b) patient circumstances including level of awareness, level of severity and family support; (c) the health and social care system including access to specialist and diagnostic services, reimbursement for diagnosis/management and availability of services and (d) cultural norms in relation to dementia including stigma, labels, and common clinical practice. The diagnosis and communication of diagnosis of dementia are intertwined processes and should be concurrently addressed in interventions. Multicomponent approaches to address these practices could include guideline development, practitioner education, anti-stigma public health campaigns, offering post-diagnosis treatments and support and sufficient reimbursement for practitioners for time spent managing dementia.